Green Support Capacity for Livestock Feed and Yield of Oil Palm Plantation in Watubangga Sub District Kolaka District - Munadi, La Ode Muhammad; Zulkarnain, Deki; Pagala, Muhammad Amrullah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This research aims to determine the support of greenery and the results of oil palm plantations as feed for Balinese cattle in Watubangga Sub District. The research method is done by observing the green potential of animal feed. Samples were obtained from the tiling of fodder greens. The research material is a group of grasses, pods, riddles, and the results of oil palm plantations. The research method analyzes weed dominance's carrying capacity and summed dominant ratio (SDR) in a specific area. The results showed nine types of greenery, two types of pods, two types of technical puzzles, and four types of plantation results as a source of livestock feed in Watubangga Sub District. The production of green dried material can meet the needs of 255.33 livestock units, and the effects of oil palm can meet the consumption needs of Balinese cattle 351,516 livestock units.